"NEO-OTTOMANISM" IN THE REGIONAL POLICY OF TURKEY (Conferencea, 2022)
This article focuses on the importance of state ideology in Turkey's foreign policy activities. The role of "Neo-Ottomanism" as a state ideology is analyzed as the main tool in determining its place in the region and the world community. he main directions of the strategy of neo are the Middle East, North Africa, Central Asia, the Caucasus, the Crimea, and the Balkans. Particular attention is paid to manifestations of neo-Ottomanism in the post-Soviet region and the Middle East, as well as "soft power" strategy in the Turkish neo-Ottomanism.